(untitled) (The Pakistan Development Review, 1969)
The literature on agricultural development and economic growth is vast and varied; it ranges from theoretical discussion of the role of agriculture in economic development to empirical studies of economic behaviour of the farm¬ers. There is, however, no agreed theory of agricultural development. Different economists hold different view-points, advance different hypotheses and provide different empirical evidence on the questions involving agricultural development and economic growth. The book under review gives a wide cover¬age of the issues, problems and complexities of agricultural development and economic growth. It is a collection of fourteen papers written by eighteen scholars who have distinguished themselves in their respective fields. Each paper has been commented upon by one or two equally reputed scholars. The author of each paper gives a critical survey of the literature on the subject and provides an extensive bibliography at the end of the paper. The topics surveyed are: agricultural development, barriers to change, infrastructure, education and training for agricultural growth, farm size and agricultural productivity, land reform, food and nutrition, marketing institutions, export of agricultural pro¬ducts, agricultural taxation, agricultural price policy, and programming of agricultural development.